Driving tourist revisit intentions to China’s heritage sites: an examination of government policies, perceived value, and technology, through the lens of satisfaction and experience - Zhifu, Tian; Jebbouri, Abdelhamid (Frontiers in Communication, 2025)
IntroductionLimited research has examined how government policies, technology integration, and perceived value simultaneously influence destination loyalty through experiential pathways. This study investigates their integrated effects on international tourists’ revisit intentions to China, with satisfaction and experience as mediators.MethodsData were collected from 508 international tourists at three Beijing heritage attractions using systematic sampling through a self-administered questionnaire. Structural equation modeling was used to test the hypothesized relationships.ResultsAll hypotheses received strong empirical support, with the model explaining substantial variance in tourist outcomes. Technology integration emerged as the primary driver of revisit intentions, while government policies and perceived value provided significant complementary effects. Tourist satisfaction and experience fully mediated the relationships between all antecedents and revisit intentions.Discussion/conclusionsFindings offer actionable insights for destination managers, policymakers, and technology developers. Organizations should prioritize digital infrastructure investments while fostering collaborative policy frameworks that enhance tourist experiences. The mediating role of satisfaction and experience highlights the importance of holistic service delivery across multiple touchpoints. This research bridges tourism studies, public policy, and technology management by providing the first integrated framework examining macro-level drivers of destination loyalty through experiential pathways, with applications extending beyond tourism to other experience-driven industries and emerging market destinations.